Analysis of planes of attacks on the Blockchain system - Stetsenko, P.I.; Khalimov, G.Z.; Kotukh, E.V. (Radiotekhnika, 2020)
This paper presents a study of attack planessurfaces and possible ways of conducting various attacks on decentralized systems based on Blockchain technology. To accomplish the task, the effectiveness of the attack is studied relative to the plane of its application, namely, relatively: cryptographic designs of Blockchain technology, distributed architecture of systems based on Blockchain technology, Blockchain application context. Several attacks have been identified for each of these planes, including malicious mining strategies, coordinated peer behavior, 51% attacks, domain name attacks (DNS), distributed denial of service attacks, delayed consensus achieving, Blockchain branching, orphaned and obsolete blocks, digital wallet thefts and privacy attacks. An attack by malicious mining allows an attacker to increase rewards by intentionally keeping his blocks closed in order to obtain a longer version of the Blockchain register than the current main version of the register. A 51% attack occurs when a single attacker, a group of nodes, or a mining pool (a combination of miners) in a network reaches most of the total processing power of mining in the system and gets the ability to manipulate the functionality of the Blockchain system. In the plane of DNS attacks, an attacker can potentially isolate peers of the Blockchain system, distribute fake blocks with fraudulent transactions among new nodes, and invalidate transactions. Manifestations of DDoS attacks can vary, depending on the nature of the functionality of the Blockchain application, the features of its network architecture and the behavior of peer nodes. Measures to counter attacks on peer-to-peer peer-to-peer architecture are considered.